Histórias de vida e desenvolvimento profissional docente de formadores na licenciatura em química: feitos, lutas e perspectivas no contexto das reformas educacionais - Wanderson Diogo Andrade da Silva (2023)
The number of researches that discuss teaching in Higher Education in Brazil has been increasing, but in the field of Chemical Education this discussion is incipient. Thus, this research starts from the following question: how university professors in the area of Chemical Education have acted in defense of the quality of teacher formation and how they position themselves in the face of changes in educational policies, especially in relation to the Base Nacional Comum de Formação de Professores (BNC-Formação) [National Teacher Training Base] and the Base Nacional Comum Curricular (BNCC) [National Common Curricular Base]? In order to seek to answer it, the general objective of the research is to investigate, based on life stories, the academic-professional trajectory of prominent university professors in the field of Chemical Education, in order to understand how they have acted in movements in defense of quality teacher formation, especially compared to the current BNC-Formação and BNCC. Based on a qualitative approach and narrative research, the research included a literature review, documentary research and the (auto)biographical method of life stories, using narrative interviews with four professors-researchers from the 1st and 2nd generation of Chemical Education brazilian linked to Federal Universities of Minas Gerais, Goiás, Rio Grande and Bahia, analyzed through Discursive Textual Analysis. The theoretical foundation discusses teacher training in Brazil in the face of educational reforms (FREITAS, 2002, 2014; DIAS; LOPES, 2003; SCHEIBE, 2004, 2008, 2011; SAVIANI, 2008, 2009, 2011; DINIZ-PEREIRA, 2013, 2015, 2016), the constitution of Chemical Education brazilian and its influence on teaching degrees and professional development (MALDANER, 1999, 2014, 2008; SCHNETZLER, 2002, 2012, 2015; MARCELO, 2009; MESQUITA; SOARES, 2011; TARDIF, 2014; PRYJMA; WINKELER, 2014; MESQUITA; SILVA, 2021), and the critical Didactics of Higher Education as the foundation of teaching (LIBÂNEO, 2006, 2008, 2013, 2017; CUNHA, 2009, 2010, 2016, 2019; FRANCO, 2012; VEIGA; SILVA, 2021). The results point out that the life story narratives allowed the trainers to reflect on their academic-professional trajectories until they became notable brazilian chemical educators. Although they entered the graduation in Chemistry with the objective of studying the bachelors, it was in the teacher formation that they consolidated their identities and professional careers working with the Chemistry teacher formation and research in Chemistry Education. Their teaching professional development processes took place through subversion strategies to oppose the bachelor's habitus of Chemistry, establishing themselves as chemical educators who see the recent educational reforms imposed in the Temer and Bolsonaro governments as harmful to the Chemistry teaching and teacher professionalization for usurping students' right to learn and teachers' work autonomy, subordinating them to the interests of capital through teaching-learning guided by the pedagogy of competences. Even though Didactics has been made invisible by the current educational reforms, the life stories report the presence of a critical Didactics of Higher Education as an integral element of the work of these trainers, contributing to a critical, reflective and innovative university teaching.